Konstruksi Demokrasi Belajar Berbasis Kehidupan pada Implementasi LMS Dan MOOC - Henry Praherdhiono; Eka Pramono Adi; Yulias Prihatmoko (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2018)
Open online-based learning which is commonly called Massive Open Online Courses (MOOC) is often studied in terms of financing, lecturers, the number of students enrolled, and the level of learning completion. However, what needs to be explained is how the MOOC is viewed from a learning democracy as a life-based learning culture, it is felt that MOOC has been able to connect thousands of learners from various backgrounds, both religion, ethnicity, race, to interests. The research was conducted using a survey method to see learners' learning experiences in learning culture in MOOC for a limited scope on the technologipend Pendidikan.org and LMS web sites with the address e-learning.um.ac.id. The results showed that the MOOC learning culture has some similarities with the learning culture in the Learning Management System (LMS).